AN ANALYSIS OF CONCEPTUAL METAPHORS OF SELF-IDENTITY AND EMOTIONAL PAIN IN TAYLOR SWIFT'S THE TORTURED POETS DEPARTMENT ALBUM - E. Faizah Cemerlang Falindy; Indah Tri Purwanti; Maria Safriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates conceptual metaphors related to self-identity and emotional pain in The Tortured Poets Department Album by Taylor Swift. The study aims to identify the types of conceptual metaphors used in the album's lyrics and explain how they represent emotional experiences and identity construction. Song lyrics were chosen because they contain figurative language that reflects complex emotional and psychological meanings. This research employed a qualitative descriptive method using Lakoff and Johnson's (2003) Conceptual Metaphor Theory, which classifies metaphors into structural, orientational, and ontological metaphors. The data consisted of metaphorical expressions found in sixteen selected songs from the album. Data were collected through documentation techniques and analyzed through identification, classification, interpretation, and conclusion drawing. The findings revealed 121 occurrences of conceptual metaphors related to self-identity and emotional pain. Structural metaphors appeared most frequently with 70 occurrences (58%), followed by ontological metaphors with 40 occurrences (33%), and orientational metaphors with 11 occurrences (9%). These findings suggest that the representation of self-identity and emotional pain in the album relied more on structured and object-based conceptualizations rather than purely spatial representations.